Internalization of Pesantren School Culture to from Students' Religious Character in SMP PGRI Brebes - Purwanto, Iman Is; Setyowati, Dewi Liesnoor; Suhandini, Purwadi (JESS (Journal of Educational Social Studies), 2022)
Currently, many students attend residential schools, private institutions, and public schools. Many students board during the day while attending Junior High School Teachers' Association of the Republic of Indonesia (SMP PGRI) Brebes from the morning till lunchtime. The purpose of this study is to identify and evaluate the contribution that schools and boarding schools make to students' assimilation of school culture and their religious character (SMP PGRI Brebes). It is a qualitative sort of study. Students, teachers, school administrators, and leaders served as study informants. In-depth interviews and documentation were employed for data collection in this study. Data collection, data reduction, data display, and conclusion retrieval are used in data analysis. The habituation and application of religious principles in the classroom and in society are the functions of schools in the establishment of religious culture in schools. The religious character traits that SMP PGRI Brebes kids can exhibit include, among others, helpful character, discipline character, courtesy character, and justice character. Students who receive support from boarding schools and from schools that instill boarding school culture show signs of internalizing religious culture in their behavior. This study is anticipated to serve as a source of information for school-based character education.